The place of Pierre Bourdieu's theories in (popular) cultural studies - Mahbub, Rifat; Shoily, Kazi Farzana (© 2016 Published by BRAC University, 2016)
This article was published in the BRAC University Journal [© 2016 Published by BRAC University]